Solidarity: Obligations and Expressions - Taylor, Ashley E. (The journal of political philosophy, 2015)
In some instances of solidarity individuals act with a group as a result of obligations incurred because of membership in that group. In other instances individuals act in solidarity to express empathy or support for a group in which they have never actually participated, and whom they could not possibly be considered to be acting with. Our options are to either accept the mutual exclusivity of these two dominant uses of the term - reject one of these views of solidarity; or to find a way of explaining that in fact both solidarity with a group and solidarity toward a group are instances of solidarity. This latter route must then explain how solidarity can bear two different normative compositions both of which are appropriately identiable as solidarity. Reprinted by permission of Blackwell Publishers